Differentiate sin(x)cos(x) using the product rule.

The product rule states (assuming x' is the differential of x): (fg)​′​​=f​′​​g+fg​′​​ Substitute the values into the rule: (sin(x)cos(x))' = sin(x)'cos(x) + sin(x)cos(x)' (sin(x)cos(x))' = cos2(x) - sin2(x)

Answered by Manibharathi P. Maths tutor

9051 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Given that: y = 5x^3 + 7x + 3. What is dy/dx? What is d^2y/dx^2?


Given log3(3b + 1) - log3(a-2) = -1 for a > 2. Express b in terms of a.


Differentiate z = e^(3y^2+5) with respect to y. (Hint: use chain rule.)


Integrate ∫x^4+5x^3+sin(2x) dx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences